2020
DOI: 10.1111/jerd.12605
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of whitening toothpaste containing blue covarine: A double‐blind controlled randomized clinical trial

Abstract: Objective: This randomized clinical trial evaluated the efficacy and safety of a blue-covarine whitening toothpaste on tooth bleaching. Subjects and methods: Seventy-five subjects with shade mean C1 or darker were randomized into three groups (n = 25): CT-conventional toothpaste, WT-whitening toothpaste, and CP10-10% carbamide peroxide. Subjects from CT and WT brushed their teeth twice/day for 2 weeks. CP10 used bleaching gel for 4 hours/night for 2 weeks. Tooth shade and CIELab parameters were measured at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 41 publications
0
30
0
4
Order By: Relevance
“…The increasing interest in the aesthetic benefits that can be obtained from dental treatment has contributed to the development of a wide variety of teeth whitening treatment products and technologies that will meet the expectations and demands. (Kielbassa, Maier, Gieren, & Eliav, 2015; Meireles, de Sousa, Lins, & Sampaio, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing interest in the aesthetic benefits that can be obtained from dental treatment has contributed to the development of a wide variety of teeth whitening treatment products and technologies that will meet the expectations and demands. (Kielbassa, Maier, Gieren, & Eliav, 2015; Meireles, de Sousa, Lins, & Sampaio, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the daily utilization of these abrasives modifies the surface of enamel and resin restorations in the mouth, decreasing the adhesion of dental plaque, food debris and chromophores, reducing tooth pigmentation, and changing its discoloration (Joiner, 2010; Vaz et al, 2019). As a new development in teeth whitening, apart from the abrasive cleaning system, using optical principles silica‐based toothpaste containing blue covarine pigment has developed (Meireles et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Recent clinical evidence supports the scarce whitening potential of toothpaste containing blue covarine after a single application 34 or even after using it for 2 weeks. 35 On the other hand, the use of BC toothpaste after in-office whitening has proven to be an effective strategy to maintain the whitening results. 36 This can be attributed to the possible synergism between BC and HP.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a few products can present in their composition a dye called Blue Covarine, which acts based on an optical approach, modifying the visual perception of tooth color by creating more light scattering, shifting the reflected color of the teeth from yellow to blue, thus creating an illusion of greater luminosity (55)(56)(57). In vitro findings suggest effective stain removal and whitening using dentifrices with Blue Covarine ( 36), but a recent clinical trial comparing a dentifrice with this dye to a control one (non-whitening) found no color improvement after a 4week period (58). The authors discussed that the Blue Covarine was able to reduce yellowness (b * parameter -CIE Lab system) after a 2-week daily treatment, with two daily applications, but this reduction did not remain stable, indicating the need for the constant application of this product to achieve acceptable results.…”
Section: Main Findings Dentifricesmentioning
confidence: 99%